Penanda Kohesi Gramatikal dalam Latar Belakang Skripsi Mahasiswa Universitas Negeri Padang - Winda Azmi (Center of Language and Cultural Studies, 2021)
This study aimed to determine the marker of what grammatical cohesion was in the background of the students’ thesis of Padang State University. The research data was in the form of written data, namely paragraphs in the background of students' thesis at Padang State University. The results in this study showed 7 theses there were 263 used of grammatical cohesion. From the analysis of the data, the most dominant marker of grammatical cohesion was the reference marker of 142 data. There were 62 data substitution markers, 38 data ellipsis markers, and 21 conjunction markers. So, it could be concluded that the writing of the background of the students’ thesis at Padang State University had a marker of grammatical cohesion which made the paragraph intact and efficient.